Ascitic fluid calprotectin and ratio of calprotectin to total protein in spontaneous bacterial peritonitis - Mai Mustafa Fahmy; Nahla Abd elAziz Nosair; Mohammed Hussien Ahmed (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the diagnostic and prognostic role of ascitic fluid calprotectin and its ratio to total protein in spontaneous bacterial peritonitis cases. Method: The prospective study was conducted at Kafrelsheikh University Hospital, Egypt, from November 2019 to December 2020, and comprised cirrhotic patients of either gender with ascites. Diagnostic abdominal paracentesis was performed for all patients and ascetic fluid calprotectin was measured. Patients were followed for development of spontaneous bacterial peritonitis or mortality. Data was analysed using SPSS 20. Results: Of the 90 patients, 61(67.7%) were males and 29(32.2%) were females. There were 67(74.4%) patients with spontaneous bacterial peritonitis; 48(71.6%) males and 19(28.3%) females with mean age 60.42±8.3 years. The remaining 23(25.5%) did not have spontaneous bacterial peritonitis; 13(56.5%) males and 10(43.4%) females with mean age 59.7±7.4 years. The patients had significantly higher calprotectin, and calprotectin/total protein ratio (p<0.05). Logistic regression identified ascitic fluid calprotectin as a significant predictor of mortality (p=0.05). The non-survivors had significantly higher ascitic fluid calprotectin and calprotectin/total protein ratio compared to the survivors (p<0.05). Conclusion: Ascites calprotectin level and its ratio to total protein was found to be accurate diagnostic and predictive biomarkers for spontaneous bacterial peritonitis. Keywords: Ascitic fluid, Ascites, Gastroenterology, Prognosis, Paracentesis, Peritonitis, Liver cirrhosis, Communicable diseases, Morbidity.